TORAKOCHIRURGIAType B thoraco-abdominal aortic dissection: strategy and possibilities of surgical treatment - Motyka, Marek; Grodowski, Mieczysław; Pachelski, Wojciech; Walas, Ryszard; Boczej, Rafał; Ruciński, Tomasz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Aim: The aim of our study was to assess the clinical effectiveness and related midterm outcome of different methods in patients with type B aortic dissection. Material and methods: The study group included 24 patients treated at our clinic. We have described the methods and strategies used in treatment of these patients, and results during a 4-year observation. Results : All the operations were technically successful, there were no intraoperative deaths. Four patients died during the observation. Two patients died due to multi-organ failure in the ICU, two and 9 days after hybrid procedures. Two other deaths occurred after the endovascular procedure. One patient died on day two due to myocardial infarction and another one six months after the procedure due to fatal stroke. Among the patients who underwent endovascular operations, in 8 cases, thrombosis of false lumen was achieved. In four patients, stable aortic dissection distally to implanted stent graft was found in CT. One patient required an additional stent graft two years after the procedure. And one patient with a leak in the proximal section of the stent graft requires an additional angio-CT three months after the procedure in order to determine treatment strategy. One patient was lost to be followed up. Patients in whom combined endovascular techniques have been used: in two CT scan presented a stable aortic dissection distally of stent graft. The patient who underwent stent graft implantation and left renal artery stenting was cured successfully. In four patients, after hybrid procedures, very good primary and secondary therapeutic results were achieved. Conclusions : Interventional individualized treatment of aortic dissection, performed in experienced medical centers, offers new treatment options for patients with this severe pathology.